2001
DOI: 10.1017/s0033822200041394
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Cosmogenic 14C: Production and Examples of its Unique Applications in Studies of Terrestrial and Extraterrestrial Processes

Abstract: Nuclear interactions of cosmic rays produce a number of stable and radioactive isotopes on the earth (Lai and Peters 1967). Two of these, 14C and 10Be, find applications as tracers in a wide variety of earth science problems by virtue of their special combination of attributes: 1) their source functions, 2) their half-lives, and 3) their chemical properties. The radioisotope, 14C (half-life = 5730 yr) produced in the earth's atmosphere was the first to be discovered (Anderson et al. 1947; Libby 1952). The next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The skull bones (including the petrous bone) preservation suggested that the animal died in the last years of the H. gigas population's existence on the Commander Islands (during the 1760s). It was impossible to conduct radiocarbon dating for this specimen due to the proximity of these dates to the present day 39 .…”
Section: Methodsmentioning
confidence: 99%
“…The skull bones (including the petrous bone) preservation suggested that the animal died in the last years of the H. gigas population's existence on the Commander Islands (during the 1760s). It was impossible to conduct radiocarbon dating for this specimen due to the proximity of these dates to the present day 39 .…”
Section: Methodsmentioning
confidence: 99%
“…The geomagnetic field deflects low-energy charged particles (Muzikar et al, 2003), affecting the cutoff energies of cosmic rays (Lal & Jull, 2001;Masuda et al, 2009). The magnetic term of the Lorentz force requires this deflection to be strongest at low latitudes, where the velocity of incoming particles is perpendicular to the geomagnetic field (Muzikar et al, 2003).…”
Section: The Need For Calibrationmentioning
confidence: 99%
“…It may seem that measurement of 14 C will be foiled by the incorporation of dissolved 14 C from seawater and the ubiquitous presence of organic matter in corals. However, in situ 14 C forms mostly 14 CO (Lal et al, 2000;Lal and Jull, 2001), making it possible to distinguish the in situ 14 C from seawater 14 C and organic matter 14 C, which would be extracted in the form of 14 CO 2 (Handwerger et al, 1999).…”
Section: Production Rates Of Useful Cosmogenic Radionuclides In Coralsmentioning
confidence: 99%